2020
DOI: 10.1101/2020.08.30.274316
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Confinement Discerns Swarmers from Planktonic Bacteria

Abstract: Powered by flagella, many species of bacteria exhibit collective motion on a solid surface commonly known as swarming. Physical changes like cell elongation and hyper flagellation have been shown to accompany swarming phenotype. Less noticeable, however, are the contrasts of collective motion between the swarming cells and the planktonic cells of comparable cell density. Here, we show that when confined by microwells of specific sizes mounted on a soft agar surface, novel bacteria Enterobacter sp. SM3 under sw… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Spatial confinement is another physical approach for inducing dynamic cell-density patterns, such as vortexes. A theoretical model of active fluidics has suggested that the confinement geometry could result in dynamic patterns, including vortex lattices [ 70 , 71 ]. While a detailed analysis is yet to be done, a similar pattern has been observed in swarming B. subtilis in a meniscus open channel, named MeniFluidics [ 72 ].…”
Section: Emerging Techniques Using Physical Stimuli For Controlling Smentioning
confidence: 99%
See 1 more Smart Citation
“…Spatial confinement is another physical approach for inducing dynamic cell-density patterns, such as vortexes. A theoretical model of active fluidics has suggested that the confinement geometry could result in dynamic patterns, including vortex lattices [ 70 , 71 ]. While a detailed analysis is yet to be done, a similar pattern has been observed in swarming B. subtilis in a meniscus open channel, named MeniFluidics [ 72 ].…”
Section: Emerging Techniques Using Physical Stimuli For Controlling Smentioning
confidence: 99%
“…Increasing cell densities enhance bacteria motility [18,50] Inhomogeneous cell density patterns of living and dead cells shape biofilm's wrinkle architecture [58] and EPS production is thickness dependent [60] Light Light drives bulk swarm motility in phototactic bacteria and blue light can slow down cells and lead to local cell accumulation [65,66] Blue light can be used to pattern biofilms in genetically engineered cells or to induce biofilm dispersal through cell hyperpolarization [74][75][76][77]79] Mechanical patterning Geometric confinement induces vortex patterns useful to identify swarming motility [70,71] 3D printing and Menifluidics can direct biofilm growth with submillimetre precision [72,[81][82][83]…”
Section: Both Swarms and Biofilms Form On Surfaces But On Surfaces With Different Mechanical Propertiesmentioning
confidence: 99%